Effect of Aerobics and Zumba on Body Fat Percentage on Young Working Women: Comparing the effects of Aerobics and Zumba on Body Fat Percentage in young working women (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the present study was to find out the effect of Aerobics and Zumba on Body Fat Percentage of 20 to 25 years old working women. Total 90 working women participated in the study, out of which 30 subjects were selected at random for the Aerobics group another 30 subjects were selected at random for the Zumba group and other 30 subjects were considered as the member of the control group. The subjects were selected from various non govt. and corporate sectors office of Salt Lake and Newtown area of Kolkata. Body Fat Percentage was measure using Bioelectrical Impedance Analysis (BIA) method. Heuer HB-301 P Body fat Analyzer equipment was used. Aerobics and Zumba training introduced for three alternative days in a week and for total duration of Twelve weeks. Pre-test and Post-test data were collected. Analysis of Covariance (ANCOVA) was conducted to identify the effect of Aerobics and Zumba on Body Fat Percentage.Results indicates that There was significant difference between both Aerobics and Zumba group with control group (p=.000), in both case p- value is less than 0.05 level of significance. But there is no significant difference between Aerobics and Zumba, because the p- value is .195 which is more than 0.05 level of significance. The study conclude Body Fat Percentage was decrease significantly after twelve weeks Aerobics and Zumba training for working women. No superiority was observed in decreasing Body Fat Percentage among Aerobics and Zumba treatment.